E-Module Based Learning as an Effort to Improve Understanding of Imla' Among Islamic Religious Education Students - Abdul Hakim; Muchdjabir Wahid (Halaqa: Islamic Education Journal, 2026)
Imla' is one of the basic skills in Arabic language learning that is important for students to master, especially in the Islamic Religious Education (PAI) Study Program. However, in practice, students' imla' ability is still low due to limited teaching materials and interactive learning methods. The purpose of this study was to analyze the effect of using e-modules on improving the understanding of imla' material. This study used a quantitative approach with a one-group pretest and posttest design. The sampling technique was purposive sampling on PAI students. The results of the analysis showed that the use of e-modules had a significant effect on improving the understanding of imla' with a p-value of 0.000. These results indicate an increase in accuracy in imla' material, namely students are able to understand Arabic writing rules and recognize mistakes that have been made previously. E-modules contribute to increasing motivation and learning independence. E-modules have also proven effective as alternative learning media in improving the understanding of imla' material for PAI students. This study recommends the development of broader e-modules and the integration of learning technology in the Arabic language curriculum in higher education. Highlights: Students demonstrated measurable gains in Arabic script comprehension after digital module use. Structured electronic materials supported clearer recognition of writing rules and errors. Technology-supported learning aligned with independent study needs in Islamic higher education. Keywords: E-Module, Imla’, Islamic Education Students